A novel design of a desiccant rotary wheel for passive ventilation applications - O'Connor, Dominic; Calautit, John Kaiser; Hughes, Ben Richard (Elsevier, 2016)
Rotary desiccant wheels are used to regulate the relative humidity of airstreams. These are commonly integrated into Heating, Ventilation and Air-Conditioning units to reduce the relative humidity of incoming ventilation air. To maximise the surface area, desiccant materials are arranged in a honeycomb matrix structure which results in a high pressure drop across the device requiring fans and blowers to provide adequate ventilation. This restricts the use of rotary desiccant wheels to mechanical ventilation systems. Passive ventilation systems are able to deliver adequate ventilation air but cannot control the humidity of the incoming air. To overcome this, the traditional honeycomb matrix structure of rotary desiccant wheels was redesigned to maintain a pressure drop value below 2 Pa, which is required for passive ventilation purposes. In addition to this, the temperature of the regeneration air for desorption was lowered. Radial blades extending out from the centre of a wheel to the circumference were coated in silica gel particles to form a rotary desiccant wheel. Computational Fluid Dynamics (CFD) modelling of the design was validated using experimental data. Reduction in relative humidity up to 55% was seen from the system whilst maintaining a low pressure drop across the new design. As an outcome of the work presented in this paper, a UK patent GB1506768.9 has been accepted.